Analyzing Metaphors of Loss in Taylor Swift’s Folklore Album Based on Conceptual Metaphor Theory - Zulfi Eka Febrianti; Ningtya Septiani (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2026)
Metaphor plays a crucial role in expressing complex emotions in literary and musical texts, particularly in representing experiences of loss that are often difficult to articulate directly. In contemporary popular music, metaphors function not only as stylistic devices but also as cognitive tools that shape how emotions are conceptualized and shared by listeners. This study aims to identify and analyze metaphors of loss in three songs from Taylor Swift’s 2020 album Folklore “My Tears Ricochet,” “Exile (feat. Bon Iver),” and “Cardigan” through the lens of Conceptual Metaphors Theory (CMT) proposed by Lakoff and Johnson (1980). Using a qualitative approach, the research applies textual and interpretive analysis to song lyrics sourced from verified platforms. The findings reveal five dominant conceptual mappings: LOSS IS A BATTLE, LOSS IS SEPARATION, LOSS IS EXILE, LOSS IS MEMORY, and LOSS IS A PHYSICAL OBJECT. These metaphors illustrate how Swift conceptualizes emotional loss through concrete domains such as warfare, distance, and tangible remnants, enabling listeners to relate to abstract emotional experiences. Each song portrays a distinct dimension of loss: conflict in “My Tears Ricochet,” displacement in “Exile,” and nostalgia in “Cardigan.” The analysis demonstrates that metaphors in Folklore function as both cognitive and emotional mechanisms that transform personal grief into shared, universal understanding. This study contributes to cognitive linguistics, literary criticism, and cultural studies by highlighting how popular music reflects universal human experiences. It also suggests pedagogical applications for integrating CMT into language and literature education to enhance students interpretive and analytical skills.